MENELAAH POLITIK LUAR NEGERI INDONESIA DALAM MENYIKAPI ISU PERDAGANGAN MANUSIA - Wuryandari, Ganewati (Jurnal Penelitian Politik, 2011)
Human trafficking remains one of the serious problemsfor Indonesia It reflects the problem oftrafficking asit is a source transit and destination state This demands stronger and more active measuresfrom the governmentto prevent and eliminate this problem How the Indonesian foreign policy to tackle the issue is the main focuss of this paper Indeed Indonesia has carried out multiple efforts to prevent and eradicate trafficking through itspolicydiplomacy and international cooperations However the problem oftrafficking continues to grow Its efforts there fore did notfully success This paper argues that human trafficking is not only a matter offoreign policy Addressing the root causes oftrafficking is also important to prevent and eradicate trafficking especially considering thedomestic and global natures of the problem